2022
DOI: 10.21203/rs.3.rs-2129508/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Naringin mitigates Bisphenol A-induced hepatotoxicity in cockerel chicks

Abstract: Bisphenol A (BPA) is an environmental pollutant, a monomer used in the polymer industry to produce plastics. BPA has been reported to cause deleterious effects in both humans and animals. Naringin is one of the flavonoids with antioxidant and metal chelating properties. This study was carried out to assess the potential ameliorative effect of naringin on BPA-induced hepatotoxicity in cockerel chicks. Thirty-one-day old cockerel chicks used for this study were randomly divided into 6 groups of five chicks per g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…This is probably because that BPA can change architecture of the liver, indicative of function defects. Our results are consistent with studies performed on rats by Ateş and Hatipoğlu, (2022) and chicken embryos by Esuola et al (2022). They found that diphenol A (100 mg/kg of body weight) caused hepatic toxicity and elevation in AST, ALT, ALP and GGT.…”
Section: Ggt Enzymesupporting
confidence: 93%
See 1 more Smart Citation
“…This is probably because that BPA can change architecture of the liver, indicative of function defects. Our results are consistent with studies performed on rats by Ateş and Hatipoğlu, (2022) and chicken embryos by Esuola et al (2022). They found that diphenol A (100 mg/kg of body weight) caused hepatic toxicity and elevation in AST, ALT, ALP and GGT.…”
Section: Ggt Enzymesupporting
confidence: 93%
“…Therefore, BPA correlated to the inflammation of liver and its diseases, such as fatty liver and nonalcoholic diseases. Hassan et al (2012) documented that BPA causes hepatotoxicity by reducing the levels of antioxidant enzymes gene expression in liver tissue, while Esuola et al (2022) showed a significant increase in the liver enzyme activity in the chick embryos exposed to BPA. The increase in liver enzymes may be attributed to damage of liver cells or other tissues, such as the heart and muscles.…”
Section: Ggt Enzymementioning
confidence: 99%